SPORTS POLICY IN INDONESIA: THE URGENCY OF PREPARING AND DEVELOPING AN OUTLINE OF THE NATIONAL SPORTS MASTER PLAN - AA, Ellectrananda sunarto; Rahmat, Doris; Faisol, Syahid Akhmad; Lumban Gaol, Indra Devian (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
Government strategy in sports development is a critical foundation for preserving public health and fitness, which in turn boosts human resource production. This process begins with culturalization through the introduction of movement from an early age, mass promotion by making sports a lifestyle, looking for superior seeds through talent scouting and strengthening sports centers through a competition system, and improving performance through coaching nationally superior sports branches so that athletes can achieve the highest achievements. Sports serve as a vehicle for physical development, but they also serve to mold the nation's identity and character by instilling qualities such as discipline, sportsmanship, dynamism, and a strong work ethic. A nation's cohesiveness, integrity, and resilience are all strengthened by sports success, which also raises the nation's prestige and dignity internationally. The concepts of efficacy and fairness are not entirely reflected in the allocation of monies. In reality, certain sports organizations with a large following and a track record of success are given fewer budgetary allotments than other organizations with less substantial contributions. In addition, excessive budget plans and insufficient organizational governance were observed in some sports that received support. These findings have strategic significance for national sports management, notably in the establishment of a performance-based funding model that can be implemented by KONI at various regional levels. This study adds to the sports management literature by presenting a complete financial evaluation framework that can be used as a resource for national sports policy reform. To ensure that available finances can support the long-term enhancement of athlete performance, financing policies must be reformulated based on performance, real needs, and institutional responsibility.